Guía descriptiva sobre el patrimonio cultural inmaterial en el ámbito cuentos mitos y leyendas en la parroquia Mulaló Cantón Latacunga - Bohorquez Sisa, Nataly Stefania (2022)
Mulaló, a parish full of history and ancestral knowledge, possessor of traditions and culture, one of the most senile parishes of the Latacunga canton, known for its neighbor the great colossal volcano Cotopaxi, calls to know about its legacy, however, during the course of time this legacy has been disappearing little by little in the daily life of the inhabitants. The present research work was performed in the Mulaló parish, Latacunga Canton, Cotopaxi Province, where oral expressions are not taken into account currently and therefore are subjected to oblivion due to lack of interest and of knowledge on the part of the inhabitants and the parish government. For the development of the research it was started from the objectives stablished to fulfill the research plan where it was begun with a chronological process to meet each goal set, thus starting with the situational diagnosis of the area, for this was based on bibliographic research which allowed to know the current state of Mulaló, leading to record different factors of the parish where population, economy, cultural identity, tourism were identified, in addition to the sectors that make up the parish, taking the Development and Land Management Plan (DLMP) as a reference for the research where a starting point was obtained to begin with the process, subsequently field trips were made to the different neighborhoods of the parish where through interviews with key actors it was possible to collect the necessary information to later be processed and inventoried through National Institute of Cultural Heritage (NICH) cards, for this point it was possible to collect within the area of traditions and oral expressions; 2 local memories linked to historical events, 3 stories, 1 myth with anthropogenic characteristics and 5 legends, one associated with supernatural elements, 1 associated with toponyms and anthroponyms, 1 associated with religious images and 3 associated with natural appearances, thus achieving a total of 11 oral expressions and most of which have presented a low sensitivity to change, this means that they are still valid but if they are not narrated over time this could adulterate their change. Finally, the information was systematized through the use of technology to obtain a descriptive guide of the cultural heritage of Mulaló in the area of stories, myths and legends. This will help to maintain and spread the oral expressions of the Mulaló parish and will help to safeguard the intangible cultural heritage, in addition it can also be used as a tool for tourism promotion.